Powassan Virus in the United States: An AI-Integrative One Health Scoping Review of Ecological Drivers, Zoonotic Interactions, Symptom Profiles, and Public Health Implications - Sarah P. Maxwell; Connie L. McNeely; James R. Harrington; Kevin C. Thomas (Infectious Disease Reports, 2026)
Background: Powassan virus (POWV) is the only tick-borne encephalitis-group flavivirus endemic to the United States (U.S.) and is an increasingly serious public health threat. Reported U.S. cases remain relatively few but have grown steadily—from fewer than two annually before 2005 to a record 60 in 2024—and neuroinvasive disease carries a 10–15% case fatality with lasting neurological sequelae in roughly half of the survivors. Examining POWV through a One Health lens, we conducted a scoping review of its ecological and zoonotic drivers, its interactions with co-circulating tick-borne pathogens, its full clinical spectrum, and its distinction from other tick-borne diseases. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidance, we searched PubMed/MEDLINE, U.S. Centers for Disease Control and Prevention (CDC) surveillance databases, state health-department publications, and vetted public-health news through early 2026. The review was conducted as an AI-integrative partnership among the authors, the Global Infectious Diseases and Epidemiology Online Network (GIDEON) database, and Claude (Anthropic), enabling a synthesis of human-curated archival records collected over six years alongside the published literature; this yielded over 200 sources, almost half unavailable through an AI search alone. Results: POWV is maintained in a sylvatic cycle involving I. scapularis ticks, small-mammal reservoirs, and incidental human spillover. Its clinical spectrum spans asymptomatic seroconversion to fatal meningoencephalitis; prodromal fever, headache, vomiting, and fatigue may progress to encephalitis, seizures, aphasia, cranial-nerve palsies, paralysis, and ataxia—the most severe neurological syndrome among U.S. tick-borne diseases. Cases cluster in the northeastern and Great Lakes states, with older males disproportionately affected, while viral evidence extends to the mid-Atlantic, southern, and western regions. POWV is distinguished by its flaviviral etiology, short (as little as 15 min) transmission window, absence of a characteristic rash, and complete antibiotic resistance. Of the 48 states surveyed, only 7 published POWV data. Conclusions: POWV is an escalating One Health threat driven by expanding vector tick ranges, land-use and climate change, and wildlife–human interface dynamics. Enhanced cross-sector surveillance integrating human, animal, and environmental monitoring, alongside improved public-health data reporting, is urgently needed.